Determinants of Port Performance - Case Study of 4 Main Ports in Indonesia (2005-2015) - Atika Aqmarina; Nuzul Achjar (Institute for Economic and Social Research, 2017)
Port plays significant role in supporting economic growth of a country. This study aims to analyze the determinant of port performance in Indonesia. In this research, the ports selected are four main ports in Indonesia which are Port of Belawan, Port of Tanjung Priok, Port of Tanjung Perak, and Makassar. These ports are designed as the hub ports in the national sea transport system of the country. The study used pooled OLS as the methodology to analyze the determinant. The result of this studies shows that total traffic is not influenced by operating surplus per ton, whereas the rest of variables such as turnaround time, idle time, berth of occupancy rate, rate of return, number of employee and cargo equipment have significant results and significantly influenced the total traffic.